How Does Taxation Affect the Economy in the Long-Run? A Study of Indian States through Panel ARDL Approach - Fayaz Ahmad Bhat; Shazia Hussain; Effat Yasmin (Statistika: Statistics and Economy Journal)
This study examines the long-term impact of taxation on economic prosperity across 20 major Indian states and union territories from 1993 to 2017. To estimate the long-term relationships, various panel autoregressive distributed lag (P-ARDL) models, including pooled mean group (PMG), mean group (MG), and dynamic fixed effect (DFE) models, are employed. Unit root tests reveal that the variables exhibit a mixed order of integration at the level and first difference. Panel cointegration tests confirm a high likelihood of a long-term cointegrating relationship among economic growth, direct taxes, indirect taxes, and social expenditure. The PMG results indicate a long-term relationship between economic growth and these variables, significant at the 5 percent level, with a cointegration rate of 1.03. In contrast, the MG and DFE estimations show cointegration rates of 1.09 and 1.07, respectively, also significant at the 5 percent level. The findings highlight a significant impact of taxation and social expenditure on economic growth in India.